KEJAHATAN DI DUNIA MAYA: PERSPEKTIF CYBERPSYCHOLOGY - Yori, Dwiana Resma (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study discusses the impact of cybercrime from the perspective of cyberpsychology. Using a descriptive qualitative approach, this research explores how the use of digital technology, particularly social media, affects individuals' mental health and behavior. Data were collected through literature review, encompassing studies related to social media addiction, digital algorithms, and other psychological impacts. The findings indicate that social media algorithms can influence users' content consumption patterns, potentially increasing stress, anxiety, and aggressive behavior. This study also highlights the importance of understanding the interaction between humans and technology to mitigate the risks of cybercrime.